Consumer Acceptance and Physicochemical Characterization of Gluten Free Muffin Containing Pumpkin Powder and Rice Flour. - Saliman, Nisa Nabila; Malik, Nur Hafizah (Enhanced Knowledge in Sciences and Technology, 2023)
Gluten-free muffin is suitable for people who are allergic to gluten, also known as celiac disease. High fiber muffins can be a good option to meet fiber deficiencies in gluten intolerance patients. Pumpkin is a great source of dietary fiber. Therefore, this study aims to assess consumer’s possible acceptance of gluten free muffins containing pumpkin powder and rice flour. A survey was conducted to 145 respondents in determination of consumer’s acceptance on gluten free muffin and utilization of pumpkin powder in gluten free muffin. Three formulations of gluten free muffin with different ratio of pumpkin powder to rice flour (80:20, 50:50, 30:70) were developed and evaluated for their physicochemical and sensory properties. Significant difference was observed between all three formulations in terms of weight, height, moisture content and cohesiveness. Muffin made with the highest ratio of pumpkin powder exhibited the increased weight, height, moisture content and cohesiveness. However, the hardness, springiness and chewiness showed no significant effect. Colour properties measured using L*, a*, b* scale revealed that the colour of gluten free muffins containing pumpkin powder was darker, redder and more yellow than wheat muffin as the level of pumpkin powder substitution increased. Sensory evaluation based on a 9-point hedonic scale among 50 panellists showed that muffin with ratio 50:50 had the highest score in appearance, taste and overall acceptance. Thus, it was selected as preferred muffin and it had 1.4% dietary fiber per 100g of muffin which is the same as muffin made from wheat flour.